Peran Zakat Dalam Mengatasi Kemiskinan: Covid-19 Di Indonesia - Rahmadita, Anisa (ITB AAS INDONESIA Surakarta, 2023)
Zakat is an obligation for a Muslim in managing their wealth and is also a form of social concern that is given when it reaches the threshold. The distribution of zakat to the recipients is not only limited to consumptive forms that meet basic human needs, but also includes productive zakat distribution in the form of capital for businesses that are monitored for their development, so that the recipients can become more self-reliant. The Indonesian economy has experienced a decline due to the Covid-19 pandemic, which has led to an increase in poverty rates in Indonesia. This research utilizes literature research from articles and published journals. The research findings indicate that zakat plays a role in alleviating poverty and ensuring social justice for the community, including during the Covid-19 pandemic. BAZNAS and LAZ throughout Indonesia have created collaborations to assist the government in dealing with Covid-19 by establishing the Covid-19 Crisis Center